Geoinformatics-Based Spatial Evaluation of Durian Cultivation in Chanthaburi, Thailand - Promproh, Kasidid; Janchomphu, Wachirathorn; Harakotr, Bhornchai; Pannucharoenwong, Nattadon (Science & Technology Asia, 2025)
Sustainable management of high-value perennial crops under climate variability requires reliable spatial tools to assess productivity and constraints. This study used geoinformatics to analyze spatial and temporal variability in durian orchard performance across Chanthaburi province, Thailand, a major production area in Southeast Asia. Multitemporal Sentinel-2 imagery (2022-2025) provided the Normalized Difference Vegetation Index (NDVI), which was integrated with yield per rai and rainfall data from ten districts. NDVI showed a strong positive correlation with yield (𝑟 = 0.74, 𝑝 < 0.01), confirming its reliability as a proxy for crop vigor and productivity. Rainfall had a moderate correlation with NDVI (𝑟 = 0.61) and a weaker one with yield (𝑟 = 0.48). The robust NDVI-yield relationship supports its use in practical yield estimation models when combined with environmental and management factors. These results demonstrate the value of remote sensing for mapping high and low yield zones, enabling precision orchard management, resource optimization, and climate resilience. Overall, the integrated geospatial framework highlights the potential of Earth observation technologies to enhance sustainable orchard practices and advance food security, climate adaptation, and environmental stewardship.